Produktivita práce od dob Fredericka Winslowa Taylora až po současnost - Špičková, Markéta; Myšková, Renáta (Univerzita Pardubice, 2010)
The paper compares the classical management theory and the current status of productivity monitoring, defines indicators of productivity and characterizes the ways that can increase the productivity. The paper states ways of the productivity monitoring that is used in current practice. Also it is stated here, what changes happened in the view to productivity during the transition from industrial to knowledge society.
Keywords: classical theory of management; productivity; partial and total factor productivity; labour productivity